Study of the indications for cesarean delivery in primiparous in Barbalha-Ceará - Dayanne Rakelly de Oliveira; Mozalina Kelly Pereira Cruz (Rev Rene)
It analyzes indications for cesarean section in primigravida e users of the Unified Health System. A descriptive, document and quantitative study was applied, and conducted with hospital records (N = 123) between January and December 2008 at a referral hospital in obstetrics in Barbalha / CE. We observed in the sample, ages between 14 and 39 years old, and 56.10% were married, 73.98% lived in urban areas, 47.97% had between 8 and 11 years of study, 39.84% were students and 32.52% farmers. And yet, that 58.54% had at least seven prenatal care and 90.24% had gestational age at delivery between 37 and 41semanas. Among the indications for cesarean section, the hypertensive disorders of pregnancy accounted for 22.22% and the pregnancy complication prevalent, and cephalopelvic disproportion 36.67%, while complication of labor. The indications for cesarean section were consistent with the literature, a fact that favors the profile of maternal and child health in the city.